Implementation of Architectural Ecological Concepts in Cultural Resort Design in Coastal Area A Case Study of Kubu Beach, Pangkalanbun, Kotawaringin District, West Kalimantan - Ryan Adam Mustaqim; Endang Setyawati Setyawati (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
AbstractThe issue of global warming and its impact on the environment requires urgent consideration from the profession of architecture. One of the ideas for using the notion of ecology as an application and reaction to the issue of environmental harm is to create tourism destination amenities in the form of resorts in coastal areas. The issue that planners face is how to keep the resort building's architecture in keeping with the site's culture. The implementation of the concept of architectural ecology was employed in the design of the resort building on Kubu beach, based on the existing challenges. The implementation is carried out by attempting to keep the place cultivated as a green space. The Resort on Kubu Beach, which is one of Kotawaringin Regency's green space areas (GSA), incorporates the notion of architectural ecology into its design, both in terms of outdoor space and residential buildings and facilities. One of the design solutions is to make use of the natural environment while still providing the modern amenities that today's society requires.Keywords: site culture resort, architecture ecology